El Zapatero y los duendes = The Shoemaker and the elves - Bailer, Darice; Serra, Sebastia; Domingues, Madelca; Grimm, Jacob, 1785-1863.; Grimm, Wilhelm, 1786-1859. (New York : Scholastic, 2007)
A retelling of the classic tale of a kindly but poor shoemaker who gets unexpected help with his work.
Spanish adaptation of the Grimm's fairy tale.
Keywords: Fairy tales; Folklore; Spanish language materials -- Bilingual